2015
DOI: 10.1371/journal.pone.0123721
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Inhibits Growth of Human Glioblastoma Cells and Enhances Therapeutic Response

Abstract: High-grade gliomas, glioblastomas (GB), are refractory to conventional treatment combining surgery, chemotherapy, mainly temozolomide, and radiotherapy. This highlights an urgent need to develop novel therapies and increase the efficacy of radio/chemotherapy for these very aggressive and malignant brain tumors. Recently, tumor metabolism became an interesting potential therapeutic target in various cancers. Accordingly, combining drugs targeting cell metabolism with appropriate chemotherapeutic agents or radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
169
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(181 citation statements)
references
References 58 publications
8
169
1
3
Order By: Relevance
“…In contrast, temozolomideinduced cell death did not implicate caspase-3 activation, suggesting the involvement of other modes of cell death, such as autophagy [72]. Autophagy is usually reduced in cells with a large number of lipid droplets, which could partly explain the limited effectiveness of temozolomide against glioblastoma tumors [73,74].…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, temozolomideinduced cell death did not implicate caspase-3 activation, suggesting the involvement of other modes of cell death, such as autophagy [72]. Autophagy is usually reduced in cells with a large number of lipid droplets, which could partly explain the limited effectiveness of temozolomide against glioblastoma tumors [73,74].…”
Section: Discussionmentioning
confidence: 95%
“…Metformin reduced proliferation in hPASMCs consistent with the antiproliferative effects of metformin reported in other cell types, (MCF7s and glioma cells in cancers). 32,33 We considered possible mechanisms by which metformin could be exerting its therapeutic and antiproliferative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular Physiology and Biochemistry studies [18][19][20][21] have shown that metformin inhibited the proliferation of various types of tumour cells, including PC cells. In our study, we first found that metformin inhibited PSCs proliferation.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%